A photopolymerizable thermoplastic with tunable mechanical performance. Issue 3 (29th November 2019) - Alim, Marvin D.; Childress, Kimberly K.; Baugh, Neil J.; Martinez, Alina M.; Davenport, Amelia; Fairbanks, Benjamin D.; McBride, Matthew K.; Worrell, Brady T.; Stansbury, Jeffrey W.; McLeod, Robert R.; Bowman, Christopher N.
Abstract : Semicrystalline polymeric materials possessing extraordinary mechanical properties were rapidly fabricated using light from low viscosity liquids at room temperature. Abstract : Semicrystalline polymeric materials possessing extraordinary mechanical properties were rapidly fabricated using light from low viscosity liquids at room temperature. Unlike conventional photopolymerizations which form crosslinked networks, this material is a noncrosslinked polymer which renders it meltable and intrinsically reprocessable. This introduces a new class of high performance, recyclable materials applicable for light-based additive manufacturing.